NUTRIENT DIGESTIBILITY AND BLOOD PROFILE OF UDA RAMS FED GRADED LEVELS OF DESERT DATE (Balanites aegyptiaca) LEAVES SUPPLEMENTED TO SORGHUM STOVER - Abdullahi, U.; Maidala, A.; Lawan, A.; Abdullahi, A. M.; Magaji, I. M.; Buhari, M. K.; Saidu, I.; Abdulsalam, M.; Mujitaba, M.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the effect of varying levels of Balanites aegyptiaca leaf meal (BLM) inclusion on nutrient digestibility and blood profile of Uda rams at the Department of Animal Science, Teaching and Research Farm, Federal University Gashua, Yobe State. Sixteen Uda rams with an average weight of 15±0.15 kg were randomly allocated to four dietary treatments containing graded levels of BLM at 0%, 5%, 10%, and 15%, with four rams per treatment. The rams were individually fed the supplemental diet at 3% of their body weight, while the sorghum stover basal diet was offered ad libitum daily for twelve weeks in a Completely Randomized Design (CRD). Each ram served as a replicate. Results from the feeding trials indicated that, the apparent digestibility of crude protein (83.91%), crude fibre (74.82%), and nitrogen-free extract (60.19%) were significantly (P<0.05) higher in rams fed 15% BLM. The results of the haematological analysis revealed a significant (P<0.05) difference in all parameters analysed, except for haemoglobin, PCV, and MCV. It was concluded that incorporating BLM at 15% in the diet of growing Uda rams enhanced their growth performance without adversely affecting haematological and serum chemistry parameters.